ANALISIS ISI PESAN DAKWAH DALAM NOVEL BIDADARI UNTUK DEWA KARYA ASMA NADIA - Imam Turmudzi; Ahmad Asrof Fitri (Melati Institute, 2022)
Da'wah values in a literary work can always be packaged by the author. The novel of Bidadari untuk Dewa is one of the best seller novels based on true stories from the ups and downs of the lives of young couples, such as debt problems, business problems, women, friendship to near-death experiences. This story is a story from the life of a young businessman named Dewa Eka Prayoga. At a very young age of 21 years, he was able to make 1 billion. Even so, he was then involved in a problem because of debts of 7.7 billion due to being betrayed by his business partners. Not only that, Dewa again faced life problems in the form of a deadly disease called Guillain Barre Syndrome (GBS) which almost made his life end. At the end of the test which almost extinguished all his defenses, he rose to fight with the spirit and strength of prostration and total surrender to the Almighty. In this spirit, Dewa tried to remain upright and earnest to repent to God. Based on the background above, the purpose of this study was to find out what the contents of the da'wah message contained in the Bidadari untuk Dewa novel by Asma Nadia and what is the dominant da'wah message in the novel of Bidadari untuk Dewa by Asma Nadia. The methodology used in this study was a quantitative content analysis method with a descriptive approach. In processing the data, it was carried out by using coding sheets filled by three judges were used in which the three judges were predetermined. After calculating the data based on the coding sheet containing 262 samples that have been filled by the three judges, the results obtained are as follows: (1) In the novel of Bidadari untuk Dewa there are 97 aqidah or creed da'wah messages, 45 sharia da'wah messages and 120 moral da'wah messages. Furthermore, from the number of da'wah messages it can be concluded that: (2) The most dominant da'wah messages in the novel of Bidadari untuk Dewa are moral messages with a percentage of 45.80%, followed by aqidah message with a percentage of 37.02% and finally the sharia message with a percentage of 17.18%.